52. Audio/ Videoconferencing Packages: High cost - Murillo, Sonia; Rizzuto, Mary; Sawyers, Urel (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
This report compares two integrated course delivery packages: Centra 6 and WebEx. Both applications feature asynchronous and synchronous audio communications for online education and training. They are relatively costly products, and provide useful comparisons with the two less expensive products to be evaluated in the following report #53. The criteria used in the current evaluation include capacity, interactivity features, integration with learning management systems, technical specifications, and cost. The report ends with a short analysis of the currently emerging audio-conferencing software, Google Talk.